Alveolar ridge reconstruction and/or preservation using root form bioglass cones - (:unkn) unknown (MUNKSGAARD INT PUBL LTD, 1998)
Extraction of a tooth necessitated by factors such as developmental problems, trauma, severe periodontal disease and endodontic problems often causes deformities of the residual alveolar ridge in the maxillary anterior region. These cases are usually difficult to restore prosthetically and they result in poor esthetics and insufficient occlusal function. This study investigated the efficacy of root form bioactive glass cones implanted into (a) artificial sockets produced by bone splitting of previous extraction sites (group BS) and (b) fresh extraction sockets (group FES). We included conventional extraction sockets sutured without implanting the root form bioactive glass cones as a control (group C). A total of 16 patients were treated for whom extractions had been indicated due to severe periodontitis. 6 patients with 7 implant sites having Class II or III alveolar ridge deformities comprised the BS group. 5 patients with 10 implant sites comprised the FES group. Group C, comprised 5 patients with 10 extraction sites. Alveolar ridge width and height measurements were obtained using study casts preoperatively, immediately postoperatively, and at 3 and 12 months after operation. In the BS group, while the width of the alveolar ridge increased by 2.8+/-1.18 mm immediately after ridge augmentation procedure and by 2.4+/-0.93 mm at 1 year after operation (p<0.01), the height of the alveolar ridge increased by 1.8+/-1.99 mm and 1.4+/-1.74 mm respectively (p<0.05). In the FES group, the differences between preoperative original ridge height and width and postoperative measurements were not statistically significant, which demonstrated the efficiency of this method in preserving the alveolar ridge. In group C, while alveolar ridge width after 12 months had not significantly changed, alveolar ridge height decreased significantly (1.35+/-1.05 mm, p<0.01). After 12 months, no dehiscences were detected and the differences in height between the groups remained significant. The results of this study indicate that this procedure is efficient in reconstructing alveolar ridges deformed as a result of extraction, particularly relevant in relation to preparation for subsequent restorative treatment.
Keywords: alveolar ridge augmentation; ridge deformities; root form bioactive glass; bone splitting; BIOACTIVE CERAMICS; AUTOGENOUS BONE; HYDROXYLAPATITE; AUGMENTATION; DEFECTS; HYDROXYAPATITE; MAINTENANCE; DOGS